Generation of chiral solitons in antiferromagnetic chains by a quantum quench - Bravo, Barbara (2013)
We analyze the time evolution of a magnetic excitation in a spin-12 antiferromagnetic Heisenberg chain after a quantum quench. By a proper modulation of the magnetic exchange coupling, we prepare a static soliton of total spin 12 as an initial spin state. Using bosonization and a numerical time-dependent density matrix renormalization group algorithm, we show that the initial excitation evolves to a state composed of two counterpropagating chiral states, which interfere to yield ⟨Sz⟩=14 for each mode. We find that these dynamically generated states remain considerably stable as time evolution is carried out. We propose spin-Peierls materials and ultracold-atom systems as suitable experimental scenarios in which to conduct and observe this mechanism.